PENGARUH CONTENT GRATIS ONGKIR DAN ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN SKINCARE SOMETHINC DI SHOPEE (STUDI KASUS MAHASISWA KOTA JEMBER) - Alizah, Aprilia Ulva Noer; Supeni, Retno Endah; Setianingsih, Wahyu Eko (Jurnal Manajemen Dayasaing, 2025)
Abstract Along with the development of the internet and technology that has an impact on changes in consumer behavior, one of which is purchasing behavior, namely shopping online. The change in purchasing behavior has made the marketplace platform grow rapidly, one of the marketplaces that consumers choose to buy products is Shopee. Factors such as content marketing, free shipping, and online customer reviews can influence online purchasing decisions. This study was conducted to analyze the influence of content marketing, free shipping, and online customer reviews on the purchasing decision of Somethinc skincare on the Shopee marketplace with a case study of Jember City students. The method in this study uses a quantitative approach through a questionnaire with a total sample of 190. The results of the study obtained the results of content marketing significantly influencing purchasing decisions (sig.0.001, t count 4.440> t table 1.972), free shipping variables significantly influence purchasing decisions (sig.0.001, t count 4.380> t table 1.972), and online customer reviews significantly influence purchasing decisions (sig. 0.000, t count 3.692> t table 1.972). The results of the determination test were 67.6%, which means that 67.6% of changes in the purchasing decision variable can be explained by the three variables. The results of the study can contribute to Somethinc skincare products in determining marketing strategies to increase sales